Pengaruh Kualitas Layanan Digital Terhadap Kepuasan Pengguna Aplikasi Ovo Di Kota Mamuju - Fiqria, Indriani Nurul; Maryuni; Yeni, Hari (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
The rapid development of financial technology (fintech) has driven massive digitalization of transactions across various regions in Indonesia, including Mamuju Regency, West Sulawesi. However, digital infrastructure challenges outside Java Island often hinder the creation of an optimal user experience. This study aims to analyze the influence of digital service quality on the satisfaction levels of OVO digital wallet users in Mamuju Regency. The research method employed is descriptive quantitative, with data collection techniques involving questionnaires distributed to 45 respondents who are active OVO users in the area. Data analysis focuses on dimensions of digital service quality, including system reliability, transaction efficiency, and technical factors such as server stability and data security. The results indicate that digital service quality plays a crucial role in shaping user satisfaction, with transaction speed being the most appreciated indicator. Conversely, local network stability remains a primary concern for the community. These findings offer important implications for OVO service providers to continue strengthening digital infrastructure and expanding the merchant ecosystem in regional areas to maintain user loyalty. This study also emphasizes the importance of synergy between technology and the availability of stable telecommunications networks in regency areas.